2020
DOI: 10.1186/s12935-020-01592-2
|View full text |Cite
|
Sign up to set email alerts
|

DARS-AS1 accelerates the proliferation of cervical cancer cells via miR-628-5p/JAG1 axis to activate Notch pathway

Abstract: Background Growing evidence has indicated the vital parts of long non-coding RNAs (lncRNAs) in modulating the progression of assorted human cancers, including cervical cancer (CC). Nevertheless, the role and mechanism of aspartyl-tRNA synthetase antisense RNA 1 (DARS-AS1) have been not comprehensively illustrated in CC yet. Methods Real-time quantitative polymerase chain reaction (RT-qPCR) was exploited for assessing RNA expression while western blot for protein expression in CC cells. The cell counting kit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“… 24 Chen et al found that DARS-AS1 could promote the proliferation of cervical cancer cells via miR-628-5p/JAG1 axis. 25 However, the mechanisms by which DARS-AS1 regulates the proliferation, apoptosis and invasion in cervical cancer cells remain largely unclear. In the present study, we found that downregulation of DARS-AS1 significantly inhibited the proliferation of cervical cancer cells via inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Chen et al found that DARS-AS1 could promote the proliferation of cervical cancer cells via miR-628-5p/JAG1 axis. 25 However, the mechanisms by which DARS-AS1 regulates the proliferation, apoptosis and invasion in cervical cancer cells remain largely unclear. In the present study, we found that downregulation of DARS-AS1 significantly inhibited the proliferation of cervical cancer cells via inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Through their interaction with various cellular proteins, E6 and E7 activate Fas, MAPK, Akt, PI3K, and Wnt signaling pathways, which modulate cellular proliferation, migration, invasion, and apoptosis, as well as epithelial–mesenchymal transition (EMT) and metastasis [ 6 , 7 , 8 , 9 , 10 , 11 ], cellular processes that modulate CC progression [ 12 , 13 , 14 ]. The dysregulation in the function of proteins, signaling pathways, and cellular processes, result from altered gene expression [ 15 , 16 ]. Viral oncoproteins, the accumulation of genetic and epigenetic alterations, and post-translational modifications lead to the inactivation of tumor suppressor genes, activation of oncogenes, and increase or decrease the expression of microRNAs (miRNAs) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dysregulation of miRNAs is involved in multiple biological processes, including the proliferation, migration, differentiation, and apoptosis of cancer cells ( 37 ). miR-628-5p functions as a tumor-suppressive gene in pancreatic ductal adenocarcinoma by regulating AKT, in gastric cancer by targeting PIN1, and in cervical cancer by regulating JAG1 ( 38 40 ). However, the roles of miR-628-5p in TNBC remain unclear.…”
Section: Discussionmentioning
confidence: 99%